Correction: Ma et al. A Plant-Produced Recombinant Fusion Protein-Based Newcastle Disease Subunit Vaccine and Rapid Differential Diagnosis Platform. Vaccines 2020, 8, 122 - Fanshu Ma; Erqin Zhang; Qingmei Li; Qianru Xu; Jiquan Ou; Heng Yin; Kunpeng Li; Li Wang; Xiangyue Zhao; Xiangxiang Niu; Xueyang Li; Shenli Zhang; et al. (Vaccines)
The authors would like to make the following correction to this published paper [...]